Postmenopausal Idiopathic Spontaneous Rupture of Pyometra with Tubo-ovarian Abscess: An Atypical Presentation - Nikita Krishna; Kiran Aggarwal; Prabha Lal; Anuradha Singh (Wolters Kluwer Medknow Publications, 2024)
Spontaneous perforations in pyometra occur rarely. Incidence is only 0.01%-0.5% in gynecological patients. Tubo-ovarian abscess (TOA) is seen less in postmenopausal women amounting the 6%-18% of the total cases of TOA reported. A 52-year-old P3L3 postmenopausal woman with abdominal pain was admitted to hospital. Emergency laparotomy was performed in view of pyoperitoneum. Intraoperatively, 1000 cc of foul-smelling pus was suctioned out from the peritoneal cavity a 2 cm × 2 cm sized perforation was seen at the right fundal region of the uterus and a right sided TOA was seen extending to the uterine cavity, left sided ovary was normal. A total abdominal hysterectomy with bilateral salpingo-oophorectomy was performed. The patient got discharged on the 36th postoperative hospitalization day. Histopathological study revealed uterine purulent inflammation with no evidence of malignancy. The diagnosis of spontaneous perforation of pyometra is rarely made preoperatively and the possibility of a perforated pyometra should, therefore, be considered when elderly women suffer from acute abdominal pain. Hysterectomy and bilateral salpingo-oophorectomy may be the best choice procedure in these patients. There is probably a new trend in the epidemiology of TOA, occurring in older women who do not present the traditional risk factors for pelvic inflammatory disease and TOA.